The tablet teacher: learning literacy through technology in Northern Sotho - Shiohira, Kelly (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2017)
This study evaluates the efficacy of the Bridges to the Future Initiative - South Africa 2 (BFI) tablet program on early literacy skills, as well as the ways in which learner-operated technology interacts with a traditional South African education system. The BFI is a curriculum-aligned early literacy development intervention implemented through technology in grades 2 and 3 in Northern Sotho1 first-language schools. A mixed-methods research design was utilized, involving three components: a literacy skills test administered through a time sequence trial design; a curriculum-aligned uptake and retention test using a pre-post design; and a qualitative research component including classroom observation, participant interviews and prompted drawings by learners. Paired sample t-tests show significantly higher gains during the treatment period in fluency and comprehension, and significantly higher gains in the control period in decoding individual words. It is theorized that this is due to teacher emphasis on emergent literacy. When initial ability is taken into consideration, all ability levels gain more on average during the treatment period in at least one measured skill. Regression analysis determines that time spent on the BFI program is not the most significant determiner of gains in the intervention period. Qualitative analysis supports this finding and suggests that program use cannot replace quality classroom practice in advancing literacy skills. Learners performed better after a delayed retention period than in an initial uptake test, indicating high rates of retention of knowledge gained through program use and traditional instruction, but inconsistent access to literacy skills gained.
Keywords: Uncatalogued